Implementasi Metode Muraja’ah Untuk Keberhasilan Menghafal Dalam Program Tahfidz Al-Qur’an Santri Di Pondok Pesantren Thoriqul Ulum Made Lamongan - Faizin Muflich, Moch; Ach Setiawan Joedi (Universitas Islam Lamongan, 2025)
This research examines the application of the muraja'ah method in the Qur'an memorization program at Thoriqul Ulum Made Islamic Boarding School, Lamongan. The implementation process is divided into three main stages: planning, implementation, and evaluation. The planning stage is arranged systematically through the establishment of programs, responsible persons, and schedules that are integrated with santri activities to ensure the continuity of memorization. In the implementation stage, muraja'ah activities are carried out individually or in groups, starting with a structured opening and closing with motivation from the supervisor to maintain the spirit of the students. Evaluation is carried out regularly to assess the accuracy and fluency of memorization, both through mentors and peer-review. The results showed that this strategy is effective in strengthening the memory and quality of the students' memorization, as well as making a positive contribution to achieving the educational goals of tahfidz Al-Qur'an in the pesantren